The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/jom.0000000000001106
|View full text |Cite
|
Sign up to set email alerts
|

Human Semen Quality, Sperm DNA Damage, and the Level of Reproductive Hormones in Relation to Urinary Concentrations of Parabens

Abstract: This is one of the first study on this topic, so the observation of the relationship between parabens and semen quality warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 28 publications
0
32
1
Order By: Relevance
“…Previous studies have demonstrated that disorders of sex hormones result in male infertility. For instance, changes in FSH, LH, and T levels are associated with damage to the testes, impeding of spermatogenesis and maturation, and result in decreased sperm motility and activity, leading to infertility [43][44][45] . This finding also exhibits strong correlation with the change in microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that disorders of sex hormones result in male infertility. For instance, changes in FSH, LH, and T levels are associated with damage to the testes, impeding of spermatogenesis and maturation, and result in decreased sperm motility and activity, leading to infertility [43][44][45] . This finding also exhibits strong correlation with the change in microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Samples which concentration exceeded the highest point of calibration curve were reanalyzed using smaller volume of urine. The limit of detection for MP, EP and PP was 0.5 ng/ml and for iBuP and BP 1.0 ng/ml [20]. The within-and between-day imprecision was 20 and 8% for MP and EP and 5% for PP, iBuP and BP, respectively.…”
Section: Urinary Parabens Measurementsmentioning
confidence: 91%
“…Parabens are extensively used as antimicrobial preservatives in food, cosmetics, toiletries and pharmaceuticals [29]. According to our knowledge only 3 studies examine the association between exposure to parabens and reproductive hormones in the case of men [17,30,31]. [38,39] indicated that there was an inverse association between urinary metabolites of non-persistent insecticides and reproductive hormones levels.…”
Section: Parabens and Male Reproductive Hormonesmentioning
confidence: 99%
“…Some authors [18,20,26] also revealed that exposure to phthalate was inversely associated with E 2 and free androgen index. Three studies [17,30,31] assess the relationship between exposure to parabens and male reproductive hormones levels and only in the study performed by Jurewicz et al [31] the level of urine BP was negatively associated with testosterone. Two of the studies [17,30] found no evidence for this association.…”
Section: Exposure Assessmentmentioning
confidence: 99%
See 1 more Smart Citation